Document synthese sur l'acces et le partage des avantages issus de l’utilisation des ressources genetiques (APA) et des connaissances traditionnelles associees au Benin - Toussaint, M.; Bienvenu, B. (2018)
These guidelines introduce the legal instruments and systems established in Benin for the mutually supportive implementation of the International Treaty and the Nagoya Protocol, describing the public bodies involved in the administration of these laws. The guidelines also include how to steps for access seekers applying for access to plant genetic resources in Benin, including forms and templates to be completed when submitting requests. Very significantly, these guidelines were co-developed by the two lead agencies responsible for the administration of the International Treaty and the Nagoya Protocol respectively.